O que alivia a minha dor: experiências de adolescentes com histórico de autolesão sobre o que traz sustentação (holding) - Costa, Luiza Cesar Riani (Universidade Federal de São Carlos, 2022)
There is a vast body of literature dedicated to the study of self-injury in adolescence, but there is a lack of research that includes them in the health promotion, that values their knowledge and experiences about what sustains them and about what makes them survive in the midst of stories filled with pain. There is also a lack of participatory, creative and artistic approaches, and it is in these gaps that we understand the need for this study. The main objective of this thesis was to understand adolescents with a history of self-injury experiences of holding, from the perspective of the Winnicottian theory. Using the Photovoice methodology and the question “What relieves your pain?” nine female adolescents with a history of self-injury photographed what sustained them. Data was analyzed using reflective thematic analysis and the results are presented in four themes. The first theme, “Everyone has their own ways” talks about the importance of embracing individuality and diversity, recognizing that there are no one-size-fits-all explanations or solutions. The theme “We there together” points to the community and relational components of holding. The third theme “Nature is feeling yourself” brings together photographs and narratives of the value of being in contact with nature. Finally, the theme “A remedy beyond what I could imagine” presents the value of bodily, sensory and artistic experiences for health promotion. The participants presented photographs that talked about affection, life, community and art, and challenged society's assumptions about youth. This work brings practical contributions by describing the implications of the winnicottian perspective for self-injury care; by pointing out photovoice as a research and intervention tool; by shedding light on the need for interventions that are contextualized, supporting, promote physical and artistic experiences, and involve nature, animals and the community; and, finally, by presenting a brochure to be used in interventions with adolescents who self-injure. I conclude the work by critically positioning the role of neoliberal, patriarchal, colonialist, racist and violent society in sustaining adolescence and preventing self-injury and suicidal behavior. We present deep and nuanced ways of thinking about self-injury and what it can mean and suggest that caring for adolescents who self-injure is more about exploring these nuances than about abstinence. We suggest implications for research and practice with adolescents who self-harm, towards less pathologizing and stigmatizing, more respectful, creative and inclusive approaches.
What relives my pain: self-harming adolescents' experiences of holding
Keywords: Autolesão Não Suicida; Adolescência; Psicanálise; Photovoice; CIENCIAS DA SAUDE